Insight into the phytochemical profile and antimicrobial activities of Amomum subulatum and Amomum xanthioides: an in vitro and in silico study - Alruhaili, Mohammed H.; Almuhayawi, Mohammed S.; Gattan, Hattan S.; Alharbi, Mohanned Talal; Nagshabandi, Mohammed K.; Jaouni, Soad K. Al; Selim, Samy; AbdElgawad, Hamada (Frontiers in Plant Science, 2023)
The current study aims to shed light on the therapeutic potential of Amomum subulatom and Amomum xanthioides fruits by analyzing the phytochemical composition of their seeds and fruits using gas chromatography-mass spectrometry (GC-MS) and high-performance liquid chromatography (HPLC) techniques to determine the presence of bioactive components such as flavonoids, phenols, vitamins, steroids, and essential oils. The protein content is usually higher than the total lipids in both species except the fruit of A. subulatum which contains more lipids than proteins. The total protein contents for A. subulatum were 235.03 ± 21.49 and 227.49 ± 25.82 mg/g dry weight, while for A. xanthioides were 201.9 ± 37.79 and 294.99 ± 37.93 mg/g dry weight for seeds and fruit, respectively. The Carvacrol levels in A. subulatum is 20 times higher than that in A. xanthioides. Lower levels of α-Thujene, Phyllanderenes, Ascaridole, and Pinocarvone were also observed in both species. According to DPPH assay, the seed extract of A. subulatum exhibited the highest antioxidant activity (78.26±9.27 %) followed by the seed extract of A. xanthioides (68.21±2.56 %). Similarly, the FRAP assay showed that the highest antioxidant activity was exhibited by the seed extract of the two species; 20.14±1.11 and 21.18±1.04 µmol trolox g−1 DW for A. subulatum and A. xanthioides, respectively. In terms of anti-lipid peroxidation, relatively higher values were obtained for the fruit extract of A. subulatum (6.08±0.35) and the seed extract of A. xanthioides (6.11±0.55). Ethanolic seed extracts of A. subulatum had the highest efficiency against four Gram-negative bacterial species which causes series human diseasesز In addition, P. aeruginosa was also inhibited by the fruit extract of both A. subulatum and A. xanthioides. Lastly, we have done detailed molecular modeling studies in silico to look at how these plants work and found that their antimicrobial effects could be due to the high binding affinity of their bioactive compounds for the active sites of the sterol 14-alpha demethylase and the transcriptional regulator MvfR. These results show that the two species have a lot of biological activities and nutritional value, which could make them useful in a number of therapeutic settings.